A case study of the causes of urban poverty in Kampung Chubadak, Sentul / Anatasha Faiza Johari and Zuhaila Muhamad - Johari, Anatasha Faiza; Muhamad, Zuhaila (2010)
Urban poverty introduces to a disastrous impact to our country. Poverty in the urban area can bring health effect, environmental effect and social decay to the community. This study made effort to determine the causes of urban poverty in Kampung Chubadak by analyzing the characteristics of the poor people. The overall purpose of the study was to identify whether the residents in Kampung Chubadak Sentul are categorized as urban poor based on the data collected. Data were randomly selected from the households in the Kampung Chubadak area and the questionnaires were distributed from door-to-door. Some interviews towards the households also have been conducted and recorded. Findings indicate that there are significant correlation between causes of urban poverty and socio-economic factor. On the whole, respondents perceived level of education, household income, and the household size as important factors to increase their quality of life and escape from being the people that fall below the PLI line.